Effect of Moxibustion on Inflammatory Cytokines in Animals with Rheumatoid Arthritis: A Systematic Review and Meta-Analysis. (8th September 2020) - Zhong, Yu-mei; Cheng, Bo-; Zhang, Lin-lin; Lu, Wen-ting; Shang, Ya-nan; Zhou, Hai-yan
Abstract : Background . This study aims to systematically evaluate the effect of moxibustion on the level of inflammatory cytokines in animal models with rheumatoid arthritis (RA) and to provide evidence for the clinical application of moxibustion to the treatment of RA and related basic researches. Methods . The databases employed in this study include PubMed, EMBASE, Web of Science, China National Knowledge Infrastructure (CNKI), Chinese Science and Technology Periodical Database (VIP), SinoMed, and Wanfang Data Information Site. The retrieval time was from the establishment of these databases to March 2020. The reviewers made use of the CAMARADES 10-item checklist to evaluate the quality of each included study. The inflammatory cytokines were considered as the outcome measure. The Revman 5.3 software was used to conduct meta-analysis on the outcome indicators of the studies included. Results . A total of 648 articles were retrieved and 18 animal experiments were included in this study. The quality scores of the studies ranged from two to eight with a mean of 5.8. Compared with the effect of the control group, moxibustion reduced the expression of TNF- α (SMD 2.95, 95% CI: 1.99–3.92, P < 0.00001 ), IL-1 β (SMD 4.10, 95% CI: 2.37–5.84, P < 0.00001 ), IFN- γ (MD 25, 95% CI: 16.17–33.82, P < 0.00001 ), IL-6 (MD 11.83, 95% CI: 6.22–17.44, P < 0.0001 ), and IL-17 (MD 99.3, 95% CI: 86.83–111.76, P < 0.00001 ). At the same time, the level of IL-2 (SMD 8.89, 95% CI: 0.93–16.86, P = 0.03 ), IL-4 (MD 1.79, 95% CI: 0.26–3.32, P = 0.02 ), and IL-10 (MD 5.93, 95% CI: 1.37–10.49, P = 0.01 ) increased after moxibustion treatment. Asymmetric funnel plots indicated that there was publication bias. Conclusion . The findings of the present review indicate that moxibustion can protect the synovium of joint in animal models with RA by upregulation of the level of anti-inflammatory cytokines and downregulation of the level of proinflammatory cytokines. Moxibustion has the potential to relieve inflammation of RA.